PENGARUH PROFITABILITAS, UKURANPERUSAHAAN, LEVERAGE TERHADAP PENGUNGKAPAN EMISI KARBON (Pada Perusahaan Pertambangan yang terdaftar di BursaEfek Indonesia Tahun 2019-2021) - Titania Neha Claudia; Bachtiar Rahman Halik (Jurnal Ekonomi dan Bisnis, 2023)
This study aims to analyze the effect of profitability, firm size, leverage on carbon emission disclosure. The population in this study are mining listed on the Indonesia Stock Exchange in 2019-2021. The population of this researce is 63 companies in the mining. The sampling method used was purposive sampling method so that 22 sample companies were optained for 3 years of observation (2019-2021) with 66 observation. Data analysis used in this study were descriptive analysis, multiple linier regression and hypothesis testing using the SPSS 21.00 program. The result of this study profitability do not effect on carbon emission disclosure while firm size and leverage have a significant effect on carbon emission disclosure.